2018
DOI: 10.1186/s13058-018-1073-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction for estrogen receptor-specific breast cancers in two large prospective cohorts

Abstract: BackgroundFew published breast cancer (BC) risk prediction models consider the heterogeneity of predictor variables between estrogen-receptor positive (ER+) and negative (ER-) tumors. Using data from two large cohorts, we examined whether modeling this heterogeneity could improve prediction.MethodsWe built two models, for ER+ (ModelER+) and ER- tumors (ModelER-), respectively, in 281,330 women (51% postmenopausal at recruitment) from the European Prospective Investigation into Cancer and Nutrition cohort. Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…42,45,46 Most of the well-known risk factors for breast cancer are related to the reproductive life of women: Women with early menarche (before age 12 years) have a higher breast cancer risk. 47 The present study found that the odds of breast cancer increase by 4 times among women with early menarche, which is consistent with studies conducted in India and Morocco. 48,49 This might be due to a woman's risk of breast cancer being related to the estrogen and progesterone made by her ovaries (known as endogenous estrogen and progesterone).…”
Section: Discussionsupporting
confidence: 92%
“…42,45,46 Most of the well-known risk factors for breast cancer are related to the reproductive life of women: Women with early menarche (before age 12 years) have a higher breast cancer risk. 47 The present study found that the odds of breast cancer increase by 4 times among women with early menarche, which is consistent with studies conducted in India and Morocco. 48,49 This might be due to a woman's risk of breast cancer being related to the estrogen and progesterone made by her ovaries (known as endogenous estrogen and progesterone).…”
Section: Discussionsupporting
confidence: 92%
“…Breast cancer is one of the most common malignant tumors in women . According to statistics, the incidence of breast cancer accounts for 7% to 10% of all malignant tumors in the body, and there are about 40 000 people died of breast cancer every year in China, which is next to uterine carcinoma . In addition, breast cancer is a malignant tumor usually occurring in the breast epithelial tissue .…”
Section: Introductionmentioning
confidence: 99%
“…The iCARE models predict risk of overall breast cancer (i.e., invasive and in situ ), rather than specific subtypes. Because risk factor associations and the effectiveness of preventive and screening strategies vary by tumor subtypes (e.g., estrogen receptor positive and negative tumors), 34-39 future work on subtype-specific risk predictions could result in more precise identification of women who would benefit most from specific interventions. Finally, the current models were derived and evaluated in studies of women of European ancestry and additional studies are urgently needed to develop and validate models for other populations, for whom alternative models have only been evaluated in relatively small studies.…”
Section: Discussionmentioning
confidence: 99%